Perbandingan Prestasi Belajar Siswa pada Mata Pelajaran IPS Sebelum Penerimaan Peserta Didik Baru (PPDB) Sistem Zonasi dan Setelah Berlakunya Sistem Zonasi - Adisel, Adisel; Sundari, Fautina (JOEAI (Journal of Education and Instruction), 2022)
The purpose of this study was to determine the comparison of student achievement in social studies subjects before the acceptance of new students (PPDB) zoning system and after the enactment of the zoning system at SMPN 2 Bengkulu City. The research method used is a quantitative method with a comparative approach. A sample of 100 students, consisting of 50 students from before the admission of new students (PPDB) zoning system and 50 students after the enactment of the zoning system, was taken by random sampling technique. and the 2020/2021 academic year where the report card scores are taken from the UAS results. Analyzed using prerequisite tests consisting of data normality test, data homogeneity and then hypothesis testing. The results of the study were that there were differences in student achievement in social studies subjects before the acceptance of new students (PPDB) with the zoning system and after the enactment of the zoning system at SMPN 2 Bengkulu City. This is based on the "z" test on the UAS scores of students in both groups, obtained zcount = 5.586 while ttable = 1.65 at a significant level of 5% which is 1.6, thus zcount > ttable (1.6 > 5.586) which means the hypothesis (Ha) in this study was accepted. In conclusion, there are differences in learning achievement in social studies subjects before the admission of new students (PPDB) zoning system and after the enactment of the zoning system at SMPN 2 Bengkulu City. Keywords: Student Achievement, New Student Admission (PPDB) Zoning System